Pertanggungjawaban Hukum Direksi Induk Terhadap Risiko Bisnis Anak Perusahaan pada Holding Company BUMN - Sindy Riani Putri Nurhasanah; Ulil Afwa (Universitas Muhammadiyah Malang, 2021)
The inability of the Limited Liability Company Law in dealing with the holding company phenomenon in Indonesia has created legal uncertainty for relevant stakeholders. Juridically, the legal status of the parent and subsidiary are separate legal entities, but the business reality shows that the parent and subsidiary are an economic entity. This status quo is even more problematic when the status of the parent company as a BUMN, where the status of state equity participation as Persero's capital has not found coherence at the normative level. This ambivalence then becomes the justification for criminalizing business risks caused by the business decisions of the board of directors. This study aims to answer the following questions: (1) What is the legal relationship between the parent and subsidiary companies in a BUMNholding company?; (2) What is the responsibility of the parent board of directors on the business risks of subsidiaries in state-owned group companies?. To answer this question, the author conducted a juridical-normative research and relied on secondary data with interpretation analysis. The results of this study indicated that: (1) Business reality shows thatthe presence of the parent and subsidiary company in the holding company is nothing more than an economic entity, which is contrary to the juridical recognition of the two business entities as separate legal entities; (2) The complexity of the relationship between the subsidiary and the parent company in the construction of a holding company, along with the dichotomous position of PMN and the lack of understanding by law enforcement officials about the theory of legal entities and the responsibilities of corporate organs, have disrupted the concept of responsibility of the parent directors towards the business risks of subsidiaries, thus giving rise to uncertainty about the responsibilities of the parent directors in state-owned group companies. Keywords: Directors; State Equity Participation; State-owned Group Company Abstrak Ketidakmampuan UU PT dalam menghadapi fenomena holding company di Indonesia telah menimbulkan ketidakpastian hukum bagi stakeholder terkait. Secara yuridis, status hukum induk dan anak perusahaan merupakan separate legal entity, namun realitas bisnis menunjukkan bahwa induk dan anak perusahaan merupakan suatu kesatuan ekonomi. Status quo ini makin problematik tatkala status induk perusahaan sebagai BUMN, di mana status penyertaan modal negara sebagai modal Persero belum menemukan koherensi dalam tatarannormatif. Ambivalensi ini kemudian menjadi justifikasi kriminalisasi risiko bisnis yangdiakibatkan oleh keputusan bisnis direksi. Penelitian ini bertujuan untuk menjawab persoalan:(1) Bagaimana hubungan hukum induk dan anak perusahaan dalam holding company BUMN? (2) Bagaimana tanggung jawab direksi induk terhadap risiko bisnis anak perusahaan pada holding company BUMN?. Untuk menjawab persoalan tersebut, penulis melakukan penelitian yuridis-normatif dan bertumpu pada data sekunder dengan analisis interpretasi. Hasil penelitian ini menunjukkan bahwa: (1) Realitas bisnis menunjukkan kehadiran induk dan anak perusahaandalam holding company tak lebih dari sebuah kesatuan ekonomi, yang mana hal ini bertentangan dengan pengakuan yuridis kedua entitas bisnis tersebut sebagai separate legal entity;(2) Kompleksitas hubungan anak dan induk perusahaan dalam konstruksi holding company disertai kedudukan PMN yang dikotomis dan pemahaman yang kurang dari aparat penegak hukum tentang teori badan hukum dan tanggung jawab organ perseroan telah mendisrupsi konsep tanggung jawab direksi induk terhadap risiko bisnis anak perusahaan, sehingga menimbulkan ketidakpastian terhadap tanggung jawab direksi induk dalam holding company BUMN.